1864
DOI: 10.1002/jlac.18641290114
|View full text |Cite
|
Sign up to set email alerts
|

Ueber die Bohne von Calabar

Abstract: In Calabar (Ober-Guinea) wird zur Beurtheilung der Verbrecher die Wirkung einer Bohne benutzt, welche, wie B a l f o u r neuerdings zeigte, der Same einer bis dahin unbekannten Leguininose ist, die B a l f o u r mit Bezug auf die eigenthiimliche Form der Narbe und die giftigen Eigenschaften der Samen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Herein, we report the first examples of molybdenumcatalyzed enantioselective allylation of any prochiral nucleophiles (eq 1) and the application of this method to the formal synthesis of (-)-physostigmine and its analogues. 6 Optimization of the ligand, solvent, and base revealed that the countercation of the base had the largest effect on the enantioselectivity of the reaction (Table 1). Bases with lithium as countercation provided the highest enantioselectivity (entries 3-9).…”
mentioning
confidence: 99%
“…Herein, we report the first examples of molybdenumcatalyzed enantioselective allylation of any prochiral nucleophiles (eq 1) and the application of this method to the formal synthesis of (-)-physostigmine and its analogues. 6 Optimization of the ligand, solvent, and base revealed that the countercation of the base had the largest effect on the enantioselectivity of the reaction (Table 1). Bases with lithium as countercation provided the highest enantioselectivity (entries 3-9).…”
mentioning
confidence: 99%
“…Then we shifted to inorganic bases at different temperatures. After exhaustive optimization we found that oxidative ethynylation of 2-oxindole methyl-3-carboxylate 4 a could easily be realized via enolalte (5)(6) in the presence of 1.2 equivalent of Cs 2 CO 3 in (CH 2 Cl) 2 solvent (entry 9) at 55°C to afford compound 7 a in 82% (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…To a stirred solution of 10 (1.20 g, 4.40 mmol) in CH 2 Cl 2 (40 mL) were added (COCl) 2 (1.15 mL, 13.2 mmol) and one drop of DMF with a Pasteur pipet, and the reaction mixture was stirred at room temperature for 4 h. All volatile materials were removed under reduced pressure to afford the crude carboxylic acid chloride, which was used for the next step without further purification. To a solution of the carboxylic acid chloride in THF (40 mL) was added NaBH 4 (499 mg, 13.2 mmol) portionwise at À30°C, and then MeOH was added (4.4 mL) at the same temperature.…”
Section: (R)-methyl 2-(2-chloro-5-methoxyphenyl)-3-hydroxy-2-methylprmentioning
confidence: 99%
“…(À)-Physostigmine (Scheme 1), 1 initially isolated from the seeds of Physostigma venenosum in 1864, 2,3 has been clinically used for the treatment of glaucoma, myasthenia gravis, atropine, and organophosphate intoxication, and for the relief of intoxication induced by overdoses of antidepressants, antihistamines, antipsychotics, and benzodiazepines. 1,4-6 (À)-Physostigmine is a potent inhibitor of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE), thereby showing wide biological activities.…”
Section: Introductionmentioning
confidence: 99%